2020
DOI: 10.1101/2020.09.25.312967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of metabolic hormone signalingviaa circadian hormone and a biogenic amine inDrosophila melanogaster

Abstract: In insects, Adipokinetic hormone is the primary hormone responsible for the mobilization of stored energy. While a growing body of evidence has solidified AKH’s role in modulating the physiological and behavioral responses to metabolic stress, little is known about the upstream endocrine circuit that directly regulates AKH release. We evaluated the AKH-expressing cell transcriptome to identify potential regulatory elements controlling AKH cell activity, and found that a number of receptors show consistent expr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…This suggests that a common regulatory theme in these metabolic networks is that hormones that regulate APCs are likely to regulate IPCs as well and vice versa. Along those lines, we recently reported that the circadian hormone, PDF, modulates APCs [ 99 ] and previous descriptions have found this peptide also targets IPCs [ 100 ]. However, the above finding suggests that endocrine and intracellular metabolic context presumably is an important aspect that governs AKH release.…”
Section: Akh Receptor Distribution and Signalingmentioning
confidence: 84%
“…This suggests that a common regulatory theme in these metabolic networks is that hormones that regulate APCs are likely to regulate IPCs as well and vice versa. Along those lines, we recently reported that the circadian hormone, PDF, modulates APCs [ 99 ] and previous descriptions have found this peptide also targets IPCs [ 100 ]. However, the above finding suggests that endocrine and intracellular metabolic context presumably is an important aspect that governs AKH release.…”
Section: Akh Receptor Distribution and Signalingmentioning
confidence: 84%
“…Yet, AKH appears to be one of presumably several factors that fine-tune locomotor activity patterns to meet physiological requirements under dietary stress-free conditions. OANs and APCs receive a multitude of converging and interconnected inputs, especially from insulin-producing cells (IPCs), with extensive feedbacks (see [70][71][72]). For example, OANs in the SEZ express receptors for AKH and DILPs, and integrate the nutritional status by responding to AKH and DILPs in an antagonistic fashion [9].…”
Section: Discussionmentioning
confidence: 99%
“…For example, OANs in the SEZ express receptors for AKH and DILPs, and integrate the nutritional status by responding to AKH and DILPs in an antagonistic fashion [9]. In turn, APCs express a range of OA receptors [72]. In addition, APCs are negatively modulated by insulin-producing cells (IPCs), suggesting feedforward signalling from IPCs to OANs via AKH signalling in parallel to direct IPC:OAN signalling [72,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11b). Therefore, based on these results and those of a previous RNA-seq analysis 39 , we surmised that NPFR is expressed in the CC. Since the CC produces the glucagon-like peptide, AKH, which regulates organismal carbohydrate and triglyceride metabolism in insects 2,20,4042 , we were particularly interested in examining whether NPFR in the CC is involved in metabolic regulation in adult D. melanogaster .…”
Section: Resultsmentioning
confidence: 62%